Prevention of aortic dissection and aneurysm via an ALDH2-mediated switch in vascular smooth muscle cell phenotype. (19th May 2020) - Yang, Kehui; Ren, Jun; Li, Xin; Wang, Zheng; Xue, Li; Cui, Sumei; Sang, Wentao; Xu, Tonghui; Zhang, Jian; Yu, Jieqiong; Liu, Zhiping; Shang, Haixia; et al.
Abstract: Aims: Aortic aneurysm/dissection (AAD) is a life-threatening disorder lacking effective pharmacotherapeutic remedies. Aldehyde dehydrogenase 2 (ALDH2) polymorphism is tied with various risk factors for AAD including hypertension, atherosclerosis, and hypercholesterolaemia although direct correlation between the two remains elusive. Methods and results: Two independent case–control studies were conducted involving 307 AAD patients and 399 healthy controls in two geographically distinct areas in China. Our data revealed that subjects carrying mutant ALDH2 gene possessed a ∼50% reduced risk of AAD compared with wild-type (WT) alleles. Using 3-aminopropionitrile fumarate (BAPN)- and angiotensin II (Ang II)-induced AAD animal models, inhibition of ALDH2 was found to retard development of AAD. Mechanistically, ALDH2 inhibition ablated pathological vascular smooth muscle cell (VSMC) phenotypical switch through interaction with myocardin, a determinant of VSMC contractile phenotype. Using microarray and bioinformatics analyses, ALDH2 deficiency was found to down-regulate miR-31-5p, which further altered myocardin mRNA level. Gain-of-function and loss-of-function studies verified that miR-31-5p significantly repressed myocardin level and aggravated pathological VSMC phenotypical switch and AAD, an effect that was blunted by ALDH2 inhibition. We next noted that ALDH2 deficiency increased Max expression and decreased miR-31-5p level. Moreover, ALDH2 mutation or inhibition down-regulated levels of miR-31-5p while promoting myocardin downstream contractile genes in the face of Ang II in primary human VSMCs. Conclusions: ALDH2 deficiency is associated with a lower risk of AAD in patients and mice, possibly via suppressing VSMC phenotypical switch in a miR-31-5p-myocardin-dependent manner. These findings favour a role for ALDH2 and miR-31-5p as novel targets for AAD therapy.